Positive Motherhood at Work: Factors Supporting a Sustainable Workforce Through Reintegration After Returning from Maternity Leave - Szabó-Cseszneki, Nikolett; Kézai, Petra Kinga; Szombathelyi, Márta Konczos (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores sustainability through the successful reintegration of women into the workforce following maternity leave. It aims to identify the key factors that contribute to positive motherhood at work and their role in building a sustainable workforce. The research is based on a systematic literature review using Scopus-indexed sources from 2006 to 2024, focusing on "maternity leave" and "wellbeing." The study applies a grounded theory approach to analyze existing organizational policies and workplace practices that influence female employees' reintegration. The findings highlight the necessity of a supportive work environment that facilitates the balance between career and motherhood. Key factors affecting reintegration include organizational policies, workplace culture, and supervisor support. The study also identifies gaps in existing research and the need for further empirical studies on reintegration practices in different industries and countries. Successful reintegration of women after maternity leave is essential for fostering a resilient and inclusive workforce. Organizations that implement supportive measures enhance employee retention, satisfaction, and overall workplace sustainability. The study's insights will inform primary research on reintegration policies in commercial banks across multiple countries. The findings will serve as a foundation for developing a model and best practices to improve the reintegration of women post-maternity leave. This research has broader implications for policymakers, HR professionals, and organizations aiming to promote gender equality and workforce sustainability.